Knowledge Cartography for Young Thinkers: Sustainability Issues, Mapping Techniques and AI Tools - Okada, Alexandra (Advanced Information and Knowledge Processing; SpringerBriefs in Advanced Information and Knowledge Processing, 2025)
Discover the transformative power of knowledge mapping with this revolutionary book. You will have access to a rich collection of mapping techniques, technologies, and real-life applications designed for learners of all ages and across disciplines. This book aims to help learners create knowledge with the support of artificial intelligence mapping apps and engage them deeply with sustainable development supported by green digital skills. Experience the dynamic world of mind maps, concept maps, dialogue maps, and more, brought to life by educators, researchers, experts, and young students. This is not just a book; it is a movement toward diverse, interactive learning methods to shape a sustainable future. Perfect for teachers, trainers, nonformal educators, and education professionals, the book embraces the innovative CARE-KNOW-DO framework to transform how young people tackle pressing issues. It combines exploration, understanding, and actionable steps for sustainability. This book offers invaluable resources to help researchers explore trends, connect relevant information, and produce significant narratives supported by AI. It guides the use of knowledge maps in decision-making, sense-making, and inspiring future generations. The book also explores the methodology behind its creation, including case studies, teaching strategies, and learning outcomes, all of which are grounded in extensive literature and ethical standards. Embrace a new era of learning with this open-access book on knowledge mapping. It is set to transform the way we think, research, teach, and learn. It is an open access book.